2022
DOI: 10.3390/molecules27061947
|View full text |Cite
|
Sign up to set email alerts
|

The SARS-CoV-2 Entry Inhibition Mechanisms of Serine Protease Inhibitors, OM-85, Heparin and Soluble HS Might Be Linked to HS Attachment Sites

Abstract: This article discusses the importance of D-xylose for fighting viruses (especially SARS-CoV-2) that use core proteins as receptors at the cell surface, by providing additional supporting facts that these viruses probably bind at HS/CS attachment sites (i.e., the hydroxyl groups of Ser/Thr residues of the core proteins intended to receive the D-xylose molecules to initiate the HS/CS chains). Essentially, the additional supporting facts, are: some anterior studies on the binding sites of exogenous heparin and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 86 publications
(156 reference statements)
0
7
0
Order By: Relevance
“…To this end, expanding the chemical space of the tested compounds by including a large variety of metal compounds is highly desirable. It has to be stressed that the search for efficient inhibitors of SARS-CoV-2-related proteases has almost entirely focused on organic molecules [ 2 , 3 , 4 ]; much less attention has been deserved so far to inorganic moieties [ 5 , 6 ] that merit, in our opinion, a greater consideration.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, expanding the chemical space of the tested compounds by including a large variety of metal compounds is highly desirable. It has to be stressed that the search for efficient inhibitors of SARS-CoV-2-related proteases has almost entirely focused on organic molecules [ 2 , 3 , 4 ]; much less attention has been deserved so far to inorganic moieties [ 5 , 6 ] that merit, in our opinion, a greater consideration.…”
Section: Introductionmentioning
confidence: 99%
“…The linear highly sulfated glycosaminoglycans units of heparin are known as heparan sulfates (HSs) [49]. Besides a variety of beneficial physiological roles derived from its binding ability at the surface of cells [50], heparins, however, particularly the heparan sulfate, act as first pathogen receptors enabling the coronavirus to anchor to its proteoglycans before interacting with the ACE2 entry receptor of the host cells (Table 1) [51][52][53][54]. Multiple binding motif sequences have been identified at different sites within the SARS-CoV-2 spike S-protein receptor-binding domain, such as the S1/S2 proteolytic cleavage motif and Y453-S459 and P681-S686, S2 ′ proteolytic cleavage S810-S816, [55,56] or near various amino acid-rich residues in different Omicron variants [57].…”
Section: Polysaccharides As Guardians: Exploring Their Potential Agai...mentioning
confidence: 99%
“…However, the versatility of heparin as an effective inhibitor of viral attachment was also suggested based on its polyanionic nature from as early as 2020 [58]. The use of soluble HS and other xyloside GAGs, such as heparin, dermatan, and chondroitin sulfates as competitive inhibitors to SARS-CoV-2, preventing the binding at the HS attachment sites, is suggested [53] based on recent evidence [59]. Preclinical evidence was brought by a series of studies that reported that exogenous heparin and derivatives such as enoxaparin can inhibit the viral infection by inducing conformational changes in the spike protein receptor-binding domain S1 in a dosedependent manner and at concentrations used during anti-coagulation therapy [59,60].…”
Section: Polysaccharides As Guardians: Exploring Their Potential Agai...mentioning
confidence: 99%
“…Trehalose can be obtained from the conversion of glucose by trehalose synthase with the action of microorganisms [20], which was effective on atherosclerosis and postinfarct cardiomyopathy [21,22]. D-xylose played a major role in hypoglycemic activity and antiviral activity [23], and the increase in its level was probably attributed to the release action from hemicellulose by fermentation on edible grass.…”
Section: Differential Metabolites Analysismentioning
confidence: 99%